Growth of rod structure with static electrical field in the Al-Ni eutectic system - Basit, Sercan; Birinci, Semih; Marasli, Necmettin (SPRINGER, 2020)
The influence of the positive and negative static electrical fields (E+ and E-, respectively) on eutectic rod spacing (lambda), eutectic grain size (EGS), hardness (HB) and ultimate tensile strength for Al-6.4 wt % Ni eutectic alloy directionally solidified from bottom to upward were investigate. The applied electric field constitutes an electrical force on liquid ions and the electrical field force leads an increment and decrement in the atomic mass flux at the solid-liquid interface when its direction is the parallel or antiparallel with solid liquid interface growth direction, respectively. Dependence of the lambda, EGS, HB and sigma(UTS )values on E+ and E- values were obtained to be lambda(+) = 2.57 x E-+(2.8)7, lambda(-) = 0.73 x E--(-1.41), EGS(+) = 362242.99 x E-+(7.75), EGS(-) = 12189.89 x E--(-4).89,HB+ = 2102.03 x E-+(-0.61),HB- = 0.602 x E--(0.63),sigma UTS+= 111.99 x E-+(-1.31) and sigma UTS- = 256.79 x E--(1.12), respectively by linear regression analysis. The exponent values of E+ and E- for EGS are higher than the exponent values of E+ and E- for lambda, HB and sigma(UTS).
Keywords: TENSILE-STRENGTH; MICROSTRUCTURE; SOLIDIFICATION; MICROHARDNESS; ALLOY; SELECTION; SPACINGS; Engineering; Materials Science; Physics